Effects of clear felling and residue management on nutrient pools, productivity and sustainability in a clonal eucalypt stand in South Africa - Dovey, Steven Bryan (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD(For))--Stellenbosch University, 2012.